VEGETATION OF THE STATE NATURAL PARK SALKYN-TOR IN THE VALLEY OF THE INNER TIEN SHAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The Naryn region in the high mountain valley of the Inner Tien Shan, due to itsgeographical location, the natural distribution of plants includes a particularly biologically diverseenvironment. The Salkyn-Tor State Natural Park, distinguished by its unique nature and harshclimatic conditions, is limited to the alpine zone, since most of the territory of the Salkyn-Tor StateNatural Park is located at an altitude of 2500-4000 m above sea level. Therefore, the types of plantschange, the physiological processes also change, and characteristic petrophilic plants appear
Keywords: landscapes, phytocenology, formation, dominant, relief, environmental factors, biodiversity, ephemera, xerophytes.